Subjective Empathy as Anthropological Link Between Experience and Truth of Faith - Cabiedas Tejero, Juan Manuel (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2023)
Christian existence is permanently faced with the challenge of strengthening the affective link between the experience of Faith and the truth of Faith. This paper tries to face this challenge through a dialogue between that peculiar human cognitive force that is empathy, and the verification that this is precisely the epistemological focus in which Gospel hermeneutics updates the meaning and salvific transcendence of the Person of Christ (dead and risen) for the witness of any time who meets Him.
Keywords: act of faith; empathy; phenomenology; Edith Stein; Christology; biblical theology